2022
DOI: 10.1038/s42003-022-03650-z
|View full text |Cite
|
Sign up to set email alerts
|

Iron limitation in M. tuberculosis has broad impact on central carbon metabolism

Abstract: Mycobacterium tuberculosis (Mtb), the cause of the human pulmonary disease tuberculosis (TB), contributes to approximately 1.5 million deaths every year. Prior work has established that lipids are actively catabolized by Mtb in vivo and fulfill major roles in Mtb physiology and pathogenesis. We conducted a high-throughput screen to identify inhibitors of Mtb survival in its host macrophage. One of the hit compounds identified in this screen, sAEL057, demonstrates highest activity on Mtb growth in conditions wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Cholesterol is a vital nutrient for Mtb in vivo (Pandey & Sassetti, 2008), and given the synergistic response of Mtb to acidic pH and Cl − (Tan et al, 2013), we anticipate that similar cross‐regulation of the Mtb acidic pH regulon by the presence of cholesterol is also likely to occur, and studies pursuing this new facet of Mtb biology are in progress. Of note, it has also been reported that the growth of Mtb in acidic pH is improved in the presence of cholesterol or even‐chain fatty acids (Baker et al, 2014; Gouzy et al, 2021), and iron limitation results in upregulated expression of Mtb cholesterol utilization genes (Kurthkoti et al, 2017; Theriault et al, 2022). Together, these findings indicate the different relationships that can exist between bacterial metabolism and environmental cue response, and future studies probing this complex aspect will undoubtedly reveal new relationships critical for bacterial adaptation to its host.…”
Section: Coordination Of Bacterial Environmental Response With Its Me...mentioning
confidence: 99%
“…Cholesterol is a vital nutrient for Mtb in vivo (Pandey & Sassetti, 2008), and given the synergistic response of Mtb to acidic pH and Cl − (Tan et al, 2013), we anticipate that similar cross‐regulation of the Mtb acidic pH regulon by the presence of cholesterol is also likely to occur, and studies pursuing this new facet of Mtb biology are in progress. Of note, it has also been reported that the growth of Mtb in acidic pH is improved in the presence of cholesterol or even‐chain fatty acids (Baker et al, 2014; Gouzy et al, 2021), and iron limitation results in upregulated expression of Mtb cholesterol utilization genes (Kurthkoti et al, 2017; Theriault et al, 2022). Together, these findings indicate the different relationships that can exist between bacterial metabolism and environmental cue response, and future studies probing this complex aspect will undoubtedly reveal new relationships critical for bacterial adaptation to its host.…”
Section: Coordination Of Bacterial Environmental Response With Its Me...mentioning
confidence: 99%
“…However, a recent macrophage infection drug screen demonstrated that one of the hit compounds limited Mtb’s access to iron by acting as an iron chelator. Mtb also has a greater dependency on iron when cultured with cholesterol as the sole carbon source, linking iron uptake and cholesterol metabolism ( Theriault et al., 2022 ). Another recent study demonstrated that iron levels play a role in modulating transcriptional responses to growth arrest when Mtb transition from exponential growth to stationary phase ( Alebouyeh et al., 2022 ).…”
Section: Lesion Microenvironments Give Rise To Non-replication and Su...mentioning
confidence: 99%
“…Additionally, the effect of iron limitation on the survival ability of Mtb has received less attention. 15,16 In this study, we attempted to generate evidence of the pivotal role played by host iron in Mtb survival and how manipulating iron availability through chemical agents, such as iron chelators, may impact Mtb clearance in both in-vitro and in vivo settings.…”
Section: Ifnmentioning
confidence: 99%